Li-Ion Battery Active–Passive Hybrid Equalization Topology for Low-Earth Orbit Power Systems - Lin Zhu; Zihua Liu; Yong Lin; Zhe Li; Jian Qin; Xiaoguang Jin; Shujie Yan (Energies)
The lithium-ion battery equalization system is a critical component in Low-Earth Orbit (LEO) satellite power supply systems, ensuring the consistency of battery cells, maximizing the utilization of battery pack capacity, and enhancing battery reliability and cycle life. In DC bus satellite power systems, passive equalization technology is widely adopted due to its simple structure and ease of control. However, passive equalization suffers from drawbacks such as complex thermal design and limited operation primarily during battery charging. These limitations can lead to inconsistent control over the depth of discharge of individual battery cells, ultimately affecting the overall lifespan of the battery pack. In contrast, active equalization technology offers higher efficiency, faster equalization speeds, and the ability to utilize digital control methods, making it the mainstream direction for the development of lithium-ion battery equalization technology. Nevertheless, active equalization often requires a large number of switches and energy storage components, involves complex control algorithms, and faces challenges such as large size and reduced reliability. Most existing active equalization techniques are not directly applicable to DC bus satellite power systems. In this study, based on the operational characteristics of LEO satellite power storage batteries, an active–passive hybrid equalization topology utilizing a switching matrix is proposed. This topology combines the advantages of a simple structure, ease of control, and high reliability. Its feasibility has been validated through experimental results.